Where is the periphery even? Capturing urban marginality in South African human rights law. (May 2019) - Pieterse, Marius
This article questions the usefulness of the notion of an 'urban periphery' for efforts to capture and ameliorate urban marginalisation and exclusion through human rights-based litigation. Focusing on South Africa's Gauteng City Region, the article argues that the notion of an urban periphery fails to capture the nuances of marginal urban life and the interests of poor, marginalised urban residents in accessing the city. In the specific context of the right of access to housing, the article then grapples with South African judicial engagements with the spatial dimensions of urban marginalisation. It finds that, despite the fixation of human rights litigators, activists and commentators on housing location and the 'urban periphery', courts are adopting a more nuanced and balanced approach to urban marginality. It accordingly identifies interests that should be accommodated by such an approach and points to legal concepts which may more constructively respond to these.